Dose-response mapping of bladder and rectum in prostate cancer patients undergoing radiotherapy with and without baseline toxicity correction - Tanuj Puri; Tiziana Rancati; Petra Seibold; Adam Webb; Eliana Vasquez Osorio; Andrew Green; Eliana Gioscio; David Azria; Marie-Pierre Farcy-Jacquet; Jenny Chang-Claude; Alison Dunning; Maarten Lambrecht; et al. (Physics and Imaging in Radiation Oncology, 2025)
Background and purpose: Radiotherapy dose–response maps (DRM) combine dose-surface maps (DSM) and toxicity outcomes to identify high-risk subregions in organ-at-risk. This study assesses the impact of baseline toxicity correction on the identification of high-risk subregions in dose–response modeling for prostate cancer patients undergoing radiotherapy. Materials and methods: The analysis included 1808 datasets, with 589 exclusions before toxicity-specific data removal. Bladder/rectum were automatically segmented on planning computed tomography scans, DSMs unwrapped into 91x90 voxel grids, and converted to equivalent doses in 2 Gy fractions (EQD2; α/β = 1 Gy). Seventeen late toxicities were assessed with two methods: (i) baseline toxicity subtracted from the maximum of 12- and 24-months toxicity scores, dichotomized at grade 1, and (ii) maximum of 12- and 24-months toxicity scores dichotomized at grade 1. DSMs were split accordingly, and voxel-wise t-values computed using Welch’s t-equation. Statistically significant voxels were identified via the 95th percentile of maximum of t-value (Tmax) distribution. Results: Event counts with baseline correction were 82/82/286/226 for urinary tract obstruction/retention/urgency/incontinence, respectively; without baseline correction, they were 93/104/465/361. For bladder DSMs, urinary incontinence, obstruction, retention, and urgency had 1143/186, 1768/1848, 516/0, and 33/0 significant voxels without/with baseline correction. For rectum DSMs, urinary incontinence and tract obstruction had 604/0 and 1980/889 significant voxels without/with baseline correction. However, no significant associations between rectal DSMs and rectum-related toxicities were found. Conclusions: DRM without baseline correction appears more sensitive to high-risk subregions due to higher event counts. Non-linear toxicity grading and multivariable analysis may enhance DRM reliability.